Role of Creative Industries in the Post-Socialist Urban Transformation - Stryjakiewicz, Tadeusz; Męczyński, Michał; Stachowiak, Krzysztof (Quaestiones Geographicae, 2014)
Over the past two decades the cities in Central and Eastern Europe have witnessed a wide-ranging transformation in many aspects. The introduction of a market-oriented economy after half a century of socialism has brought about deep social, economic, cultural and political changes. The first stage of the changes, the 1990s, involved the patching up of structural holes left by the previous system. The post-socialist city had to face challenges of the future while carrying the ballast of the past. Rapid progress in catching up with the West transformed the city a great deal. Later on, the advent of the 21st century brought a new wave of development processes based, among other things, on creativity and innovation. Hence our contribution aims to explore the role of creativity and creative industries in the post-socialist urban transformation. The article consists of three basic parts. In the first we present the concept of a ‘creative post-socialist city’ and define the position of creative industries in it. We also indicate some similarities to and differences from the West European approaches to this issue. In the second part, examples from Central and Eastern Europe are used in an attempt to elucidate the concept of a ‘creative post-socialist city’ by identifying some basic features of creative actions /processes as well as a creative environment, both exogenous and endogenous. The former is embedded in different local networks, both formal (institutionalised) and informal, whereas the structure of the latter is strongly path-dependent. In the third part we critically discuss the role of local policies on the development of creative industries, pointing out some of their shortcomings and drawing up recommendations for future policy measures.